Disturbance observer–based event-triggered tracking control of networked robot manipulator. (May 2020) - Bu, Wei; Li, Ting; Yang, Jun; Yi, Yang
We investigate the event-triggered tracking control of networked manipulator in the presence of external disturbance and a variety of system uncertainties. The event-triggered controller is designed by the nonlinear disturbance observer–based control approach, which can dynamically compensate for both errors caused by disturbances and the undesirable effects caused by event-triggering rules. A rigorous Lyapunov stability analysis method is proposed to show that the boundedness of all the signals in the closed-loop system can be guaranteed while in the absence of the input-to-state stability assumption related to measurement errors, tracking error can be constrained to an arbitrarily small set without escaping. Finally, by some simulation results, the feasibility and effectiveness of the proposed control approach is demonstrated.